The Influence of Learning Environment and Religiosity on Students' Academic Achievement in Learning Islamic Cultural History at MTs Almaarif 01 Singosari - Hani'ah, Wardatul; Aziz, Rahmat; Zuhriyah, Indah Aminatuz (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2025)
Understanding the determinants of students’ academic achievement is critical, particularly in the context of Islamic Cultural History education at the madrasah level. This study investigates the influence of the learning environment and religiosity on the academic achievement of students at MTs Almaarif 01 Singosari. Employing a quantitative approach with a correlational design, the research involved 276 randomly selected students from grades VII, VIII, and IX. Data were collected using Likert-scale questionnaires to assess students' perceptions of their learning environment and religiosity, while academic achievement was measured using report card scores. Multiple linear regression analysis revealed that both the learning environment and religiosity significantly influence academic achievement, both jointly and independently. The learning environment emerged as the more dominant predictor, with a standardized beta coefficient of 0.280, compared to religiosity with a beta coefficient of 0.163. The model's R² value of 0.146 indicates that these two variables explain 14.6% of the variance in academic achievement, suggesting that additional unmeasured factors also contribute to students' academic performance. These findings underscore the importance of fostering both conducive learning conditions and strong religious values to support educational success. The study highlights the need for a holistic educational approach that integrates physical, social, and spiritual dimensions to create a supportive and sustainable learning ecosystem in madrasah settings.